2013
DOI: 10.1371/journal.pone.0080850
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic Acid Protects against Cisplatin-Induced Nephrotoxicity without Compromising the Anticancer Efficiency of Cisplatin in Rats In Vitro and In Vivo

Abstract: Background/AimsNephrotoxicity is a frequent and major limitation in cisplatin (CDDP)-based chemotherapy. 5-Aminolevulinic acid (ALA) is widely distributed in animal cells, and it is a precursor of tetrapyrole compounds such as heme that is fundamentally important in aerobic energy metabolism. The aim of this study is to evaluate the protective role of ALA in CDDP-induced acute kidney injury (AKI).MethodWe used CDDP-induced AKI rat model and cultured renal tubular cells (NRK-52E). We divided four groups of rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 31 publications
2
39
2
1
Order By: Relevance
“…Hou et al reported that ALA had a renoprotective effect in an IRI model via upregulation of HO‐1 and suppressing expression of TNFα and macrophage infiltration . Terada et al reported that ALA upregulated HO‐1 and suppressed tubule cell apoptosis in cisplatin nephropathy . However, in our experiment, the specific HO‐1 inhibitor, ZnPPIX, did not overcome the renoprotective effect of ALA against rhabdomyolysis‐induced AKI.…”
Section: Discussioncontrasting
confidence: 73%
“…Hou et al reported that ALA had a renoprotective effect in an IRI model via upregulation of HO‐1 and suppressing expression of TNFα and macrophage infiltration . Terada et al reported that ALA upregulated HO‐1 and suppressed tubule cell apoptosis in cisplatin nephropathy . However, in our experiment, the specific HO‐1 inhibitor, ZnPPIX, did not overcome the renoprotective effect of ALA against rhabdomyolysis‐induced AKI.…”
Section: Discussioncontrasting
confidence: 73%
“…In fact, the upregulation of HO‐1 has been shown to improve glucose metabolism, and enhance insulin signalling in several animal models of diabetes, which in turn was linked to antioxidant mechanisms . 5‐ALA/SFC produced by haem induces carbon monoxide in mouse kidney by activating HO‐1, demonstrating that 5‐ALA/SFC induces HO‐1 activity. Our findings also showed that 5‐ALA/SFC upregulates HO‐1 expression in the scl‐GvHD mouse model in line with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 5‐ALA is known to induce haem oxygenase‐1 (HO‐1) in vitro and in vivo . HO‐1 acts in haem metabolism as a rate‐limiting enzyme, and the increase in HO‐1 expression generates bilirubin and carbon monoxide, which were shown to act as cytoprotective factors …”
Section: Introductionmentioning
confidence: 99%
“…5‐aminolevulinic acid (ALA) is widely used to induce protoporphyrin IX (PPIX), a photosensitizer used in photodynamic diagnosis and therapy for non‐muscle invasive bladder cancer . ALA is distributed ubiquitously in mammalian cells and is a precursor of tetrapyrole compounds such as heme, which is essential in aerobic energy metabolism and the electron transport system . ALA reportedly exerts a broad range of cytoprotective effects against cisplatin‐induced nephrotoxicity, rhabdomyolysis‐induced acute kidney injury, hypoxia‐induced cardiomyocyte injury, and low phosphorus loading‐induced neurotoxicity through its antioxidant abilities .…”
Section: Introductionmentioning
confidence: 99%